Use of mobile devices and medication errors in acute care: a systematic review protocol. (September 2016) - Harder, Nicole; Plouffe, Jannell; Cepanec, Diane; Mann, Kari; Lê, Mê-Linh; Gregory, Patricia; Griffith, Patrick; Doerksen, Kathy
Abstract : Review question/objective: The objective of this review is to synthesize the best available evidence on the effects of healthcare providers using mobile devices at any stage of medication provision on medication errors in acute care settings. Provision of medication includes prescribing, dispensing or administrating medicine in the acute care setting.